Zinner syndrome in pediatric patients: rare disease leading to challenging management - Adorisio, Ottavio; Orazi, Cinzia; Gregori, Lorenzo Maria; De Peppo, Francesco; Silveri, Massimiliano (Frontiers in Pediatrics, 2024)
Zinner syndrome (ZS) is the association of seminal vesicle cysts, ipsilateral ejaculatory duct obstruction and ipsilateral renal agenesis. This condition is very rare in children and both diagnosis and treatment may be challenging. We reviewed the clinical presentation and treatment describing our experience with a series of 3 patients.From January 2016 to January 2021, three patients (1, 2, 3) with symptomatic ZS, aged respectively 2, 15, and 17 years were diagnosed and treated. All these patients were symptomatic manifesting pelvic pain and dysuria. The diagnosis was made by physical examination, ultrasonography and abdominopelvic MRI. Patient 1 underwent to open surgery, while for patients 2 and 3 laparoscopic excision was performed.The renal agenesis regarded the left side in patients 1 and 3, and the right side in patients 2. In all cases, the cystic complex was excised. The mean operating time was 4 hours and the mean hospitalization time was 5 days (range 4-6 days). The mean follow-up period was 5 years (range 2-5 years). Patients 1 and 3 showed a complete resolution of the symptoms during postoperative follow-up. In patient 2, clinical symptoms relapsed because of the persistence of a 9 mm cyst requiring a redo laparoscopic excision.Seminal vesicle cyst with ipsilateral renal agenesis, even if rare in pediatric age, should be suspected in young male patients presenting with pelvic cystic masses, pelvic pain, dysuria and ipsilatreral renal absence.Conservative management should be reversed to asymptomatic patients. Surgical treatment is mandatory in symptomatic cases and the preferred approach is minimally invasive surgery to magnify the operating field to spare anatomical structures, primarily the contralateral vas deferens.Radicality is crucial to avoid the persistence of symptoms and the need for re-intervention.